IS SILENCE GOLDEN? CONVERSATIONS OF NATIVE SPEAKERS OF RIMI IN SINGIDA- TANZANIA - Choyo, Musa Ibrahim (UC Journal: ELT, Linguistics and Literature Journal, 2023)
This paper provides an empirical examination of the perception of silence as a communicative act in a Rimi cultural context. Four casual conversations with Rimi native speakers were examined.  Silence in conversation was determined using a turn-taking framework in Conversation Analysis previously described by Sacks et al. (1974) as a turn-taking organization.  Native speakers of Rimi like people in other cultures have beliefs and myths regarding silence. However, these cultural artifacts are often hardly reflected in their real conversation practice. Rimi's belief regarding the value of silence dictates avoidance of silence because they consider it a danger and veiled bad intentions. Despite this cultural orientation regarding silence, in some contexts, Rimi native speakers give it a positive value. The findings show that silence can be used for terminating a topic, showing agreement, and indicating emotions such as sadness. Silence therefore can lead to either harmonious or troubled conversation at the same time. Many prolific studies have shown that Eastern cultures appreciate silence while the Western cultures silence is attributed to incompetence and lack of willingness to participate in communication. This cultural dichotomy regarding the perception of silence between Western and Eastern cultures gives an impression that cultures can either perceive silence positively or negatively. Data from this study show that this understanding is faulty. The data indicate that silence cannot be described categorically as solely positively or negatively perceived in a particular culture; instead, it should be viewed as a variable entity within a single cultural group.